PENGARUH KOMPOSISI CAMPURAN TONGKOL JAGUNG DAN AMPAS TAHU TERHADAP KANDUNGAN BAHAN KERING, PROTEIN KASAR DAN SERAT KASAR PRODUK FERMENTASINYA - Ramadhani, Fath Hate; Sutrisna, Rudy; Liman, Liman; Erwanto, Erwanto (Department of Animal Husbandry, Faculty of Agriculture, University of Lampung, 2024)
This study aims to determine the effect of the composition of a mixture of corn cobs and tofu by product on the content of dry matter, crude protein, and crude fiber of fermentation products. This research was conducted on January 12 - February 03, 2023, at the Animal Nutrition and Food Laboratory, Department of Animal Husbandry, Faculty of Agriculture, University of Lampung. This study used a completely randomized design (CRD) consisting of 4 treatments and 5 replicates. The treatments were P0: 50% corn cob + 50% tofu by product (control), P1: 50% corn cob + 50% tofu by product + 4% tempe yeast, P2: 60% corn cob + 40% tofu by product + 4% tempe yeast, and P3: 70% corn cob + 30% tofu by product + 4% tempe yeast. The observed variables included dry matter, crude protein, and crude fiber. The data obtained were analyzed using Analysis of Variance (ANOVA) and continued with Duncan's Multiple Range Test (DMRT). The results showed that the composition of the mixture of corn cob and tofu by product was significantly different (P<0.05) on dry matter (P0: 34.39%, P1: 34.80%, P2: 35.98%, and P3: 36.11%, very significantly different (P<0.05) to crude protein (P0: 11.73%, P1: 15.54%, P2: 14.68%, and P3: 11.30%, and significantly different (P<0.05) to crude fiber (P0: 30,54%, P1: 27,23%, P2: 27.40%, and P3: 28,56%. The best treatment was in P1 on crude protein and crude fiber, and in P3 on dry matter.